Pertumbuhan dan Produktivitas 5 Varietas Unggul Baru Padi di Lahan Bukaan Baru Kabupaten Boven Digoel - Fajriyatus Shoidah; Adnan Adnan (Universitas Sebelas Maret, 2021)
New wetlands field generally has low productivity, so a technology is needed for improve productivity. New Superior Variety (NSV) is a technology that is considered easy to be adopted by farmers, so knowing a NSV that is able to adapt to the characteristics and conditions of new wetlands field is a must. The study of adaptive NSV on new wetlands field in Boven Digoel Regency is still limited so that the NSV recommendation for farmers is also still limited. The purpose of this study was to examine the growth and production of new superior varieties on the new wetlands fields in Boven Digoel Regency. The study was conducted on new wetlands in Asiki Village, Jair District during April-August 2019. Randomized Complete Block Design was employed with 3 replications using Inpari 36, Inpari 37, Inpago Rindang 1, Inpago Rindang 2 dan Inpara 8. The results showed different varieties perform different agronomy characters observed (plant height, number of tillers, panicle length, number of grains per panicle, filled grain, per panicle, empty grain per panicle and 1000 grain weight). Inpari 37 produced 5.3 ton/ha Dried Unhulled Rice, the highest production compared to other varieties, so that it could potentially be developed in Boven Digoel’s new wetlands field. Productivity may still be increased by improving soil fertility conditions.